Penerapan Keselamatan Dan Kesehatan Kerja (K3) Di Daya Tarik Wisata Bali Treetop Adventure Park, Bedugul - Sudana, I Made Ari; Sukana, Made (JURNAL DESTINASI PARIWISATA; Vol 6 No 2 (2018): VOL 6, NO 2 (2018): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2018.v06.i02.p04, 2019)
Bali Treetop Adventure Park is a tourist attraction, which is located in the Eka Bali Botanical Garden, Candi Kuning, Tabanan Regency. This tourist attraction offers adventure activities or adventures that are above the altitude. This research aims to know the application of Workplace Safety and Health on adventure activities in the tourist attraction of Bali Treetop Adventure Park The data used in this research is the type of qualitative data, while the data source is primary data and secondary data. Data was collected by observation, interview and literature study, and assisted by data analysis technique. The results show that the application of Workplace Safety and Health in this tourist attraction has been excellent. From the personal aspect, there is training for all the staf to improve their knowledge and skills in preventing and handling accidents, staf also asks for health conditions of tourists before attempting adventure rides, safety checks of the equipment and checking of the adventure rides is also conducted on a daily basis. From The insitutional aspect, company also divides the staf into different tasks so that staf can focus on their work. Environmental conditions such as weather conditions are also considered, during bad weather conditions this adventure vehicle will be closed. Every package purchased by tourists include the cost of insurance, in case of an accident involving the tourists then all the medical expenses will be covered by the insurance. Keyword : Occupational Safety and Health ,Adventure Tourism, Bali Treetop Adventure Park